Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) in Victims of Sexual Violence Who Experience Trauma: A Systematic Review - Nurhalimah, Nurhalimah; Hamid, Achir Yani Syuhaimie; Putri, Yossie Susanti Eka; Rachmawati, Imami Nur (JURNAL INFO KESEHATAN, 2024)
Incidents of sexual violence are like an iceberg phenomenon and continue to increase every year. However, this increase is inversely proportional to the rehabilitative efforts provided for victims of sexual violence. The impact of sexual violence is trauma that makes the victim feel helpless. Trauma-Focused Cognitive Behavior Therapy (TF-CBT) is the therapy of choice to treat these impacts. This systematic review aims to determine the implementation and benefits of TF-CBT for trauma victims of sexual violence. The search used seven databases: Scopus, Sage Journals, ScienceDirect, ProQuest, PubMed, Clinical Key, and EBSCOhost. The research design used in the selected articles was three with RCTs, 5 with Quasy experiments, and 2 with cohorts. Selection is based on the criteria of article publication time in the last ten years, providing full text in English. The symptoms measured in trauma cases are PTSD, post-traumatic symptoms, mental problems such as depression, suicide attempts, and behavioral problems. The results showed that TF-CBT positively influenced all of these symptoms. Implementing TF-CBT also involves the role of parents and modifications with culturally sensitive principles. TF-CBT can reduce trauma symptoms. It is hoped that TF-CBT can be used in other trauma cases and apply modification principles that previous researchers have carried out by being culturally sensitive and involving the role of parents.